The decision factor of car purchasing among Malaysian undergraduates - Yusof, Fatimah Az-Zahrah; Kasman, Fazela; Mak, Yoke Mun; Nallapan Maniyam, Shamini (2015)
The automotive industry is an important segment of the economy in any country as it links industry and services. So to keep on increasing automotive industry in Malaysia, every automobile producer company must understand customer decision factor to purchase the car. This study aims to find the relationship between factors that lead towards decision making on the purchasing car that focused on undergraduates of Public Higher Education Institutions. The objective of this research is to study the relationship of ‘price’, ‘quality’, ‘safety’ and ‘fuel economy’ that will effect on Malaysian undergraduates purchase decision towards cars. The data for the study has been collected from respondents via questionnaire and were distributed to 384 respondents. In this last phase, the research concludes an overall of four analyses which are Reliability, Descriptive, Correlation and Multiple Regression by obtaining good statistics. The result gained has been filtered and shows a positive outcome